Estimation and reconstruction of facial creases based on skull crease morphology. Issue 1 (2nd January 2018) - Hadi, H.; Wilkinson, C.
Abstract : This research explores the relationships between the facial creases and the morphology of the underlying skull for supplementary use during forensic facial reconstruction. The correlation between skull morphology and the patterns of facial creases was obtained using the three-dimensional (3D) skull surface scans from the William Bass skeletal collection at the University of Tennessee, USA, which also provided the related ante-mortem face photographs. Superimposition of the facial crease patterns seen in a face photograph with the related skull image enabled the visual analysis of the correlation between the crease and the skull morphology. Qualitative analysis indicated that the infraorbital crease follows the outline of the orbit in 52% of the subjects, while the nasolabial fold (NLF) relates to the canine fossa in 95% of the subjects. The infraorbital crease and NLF were reconstructed in a blind study using ten 3D surface scan skull models and related face photographs from the Helmer collection available in the Centre for Anatomy and Human Identification, the University of Dundee, UK. Correct prediction was obtained in six specimens (60%). One inconclusive result was due to poor photograph quality and three inaccurate results showed an overestimation of the NLF strength although the location of the crease manifestation was correct.